CYBER CRIME UNDER THE PROVISIONS OF IPC (International Journal of Food and Nutritional Sciences, 2022)
Law provides a cure against the vast majority of the common digital violations. 'Digital wrongdoing' is certainly not a characterized term however a catch-all expression inferable from any offense including a web gadget. The vast majority of the digital violations are recorded under the Information Technology Act (IT Act), 2000, which was amended in 2008 and 2012.Nonetheless, this lucidity vaporizes with the acknowledgment that IT Act isn't the main authorization covering digital wrongdoing. The Indian Penal Code (IPC) could likewise be brought in to start arraignment against digital violations or to enhance the arrangements of the IT Act. For example, offenses like hacking, information burglary, infection assaults, refusal of administration assaults, unlawful altering source codes including ransomware assaults could be indicted under S.66 r/w S.43 of the IT Act. Instances of producing a credit or debit .The IT Act to give legitimate acknowledgment to exchanges did by methods for electronic information trade and different methods for electronic correspondence, regularly alluded to as "electronic business", which include the utilization of choices to paper-based strategies for correspondence and capacity of data, to nusta altering electronic recording of reports with the Government organizations and further it has it provisions under the Indian Penal Code, the Indian Evidence Act, 1872, the Bankers' Books Evidence Act, 1891 and the Reserve Bank of India Act, 1934 and support matters associated there with or coincidental thereto.Even Though with sufficient laws we are still facing lot of cyber crime suits and for this the researcher had undergone a study with 1579 samples . This paper focuses on the concept of cyber crime and its provision with IPC. The online criminal activities is widespread throughout the world. From the analysis, the paper sort to conclude that the null hypothesis . There is an association between the dependent and independent variables.